Are Legal Aspects, New Normal (Covid-19), and Entrepreneurial Characteristics Important for the Growth of Higher Education Industry Performance in DKI Jakarta? - Prasetio Ariwibowo; Haryanto Haryanto; Taufik Taufik (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
This research is a quantitative research conducted to find out how big and how important is the role of business legality, New Normal (Covid-19) and the entrepreneurial character of an entrepreneur, especially on business performance in the form of market share, profitability, and business productivity, especially in the business sector of universities in Indonesia. DKI Jakarta. Determination of the sample was carried out by purposive sampling with a sample of 150 respondents consisting of lecturers, students, and several university officials in DKI Jakarta. In this study using SEM-PLS as a test analysis tool. The results of this study indicate that the entrepreneurial characteristics of business actors have a vital role in the growth of business performance, while the legal aspect of business does not have a significant influence in improving the performance of higher education institutions in DKI Jakarta, both from the point of view of profitability, market share, and business productivity.